2021
DOI: 10.1186/s40709-021-00141-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of two novel 4-MMPB analogs as potent lipoxygenase inhibitors for prostate cancer treatment

Abstract: Background Lipoxygenases are one of the critical signaling mediators which can be targeted for human prostate cancer (PC) therapy. In this study, 4-methyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-MMPB) and its two analogs, 4-propyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-PMPB) and 4-ethyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-EMPB), were proposed to have anti-tumor properties in prostate cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Fayzullin et al used a combination of CsA (30 mg/kg) and ketoconazole (10 mg/kg) to induce immunosuppression in BALB/c mice 20 . Iranpour et al suppressed the immune system of male C57BL/6 mice by combination of CsA, itraconazole and co‐amoxiclav 21 . Cunha et al reported xenotransplantation (cross‐species transplantation) of human cells of glioblastoma in rats by CsA treatment (5 mg/kg, daily) until the final step of experiments 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fayzullin et al used a combination of CsA (30 mg/kg) and ketoconazole (10 mg/kg) to induce immunosuppression in BALB/c mice 20 . Iranpour et al suppressed the immune system of male C57BL/6 mice by combination of CsA, itraconazole and co‐amoxiclav 21 . Cunha et al reported xenotransplantation (cross‐species transplantation) of human cells of glioblastoma in rats by CsA treatment (5 mg/kg, daily) until the final step of experiments 8 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Iranpour et al suppressed the immune system of male C57BL/6 mice by combination of CsA, itraconazole and co-amoxiclav. 21 23 Akhter et al reported successful induction of human colon adenocarcinoma cells in rats using daily CsA administration. 6 In this study, CsA, ketoconazole and CP drugs were used to improve an immunosuppression protocol in order to induct human tumour xenografts in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An immunosuppression protocol was carried out on male C57BL/6 mice (4-6 weeks old) as described previously. 40 The xenograft tumor model was developed by subcutaneous injection of 8 Â 10 6 HT-29 cells (suspended in 1 : 1; PBS: Matrigel) into the back of immunocompromised C57BL/6 mice. 2.9.1.…”
Section: Development Of a Xenograft Mouse Modelmentioning
confidence: 99%
“…Besides, scientists have artificially synthesized some ferroptosis inducers. 4-methyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-MMPB) and its two analogs, 4-propyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-PMPB) and 4-ethyl-2-(4-methylpiperazinyl)pyrimido[4,5-b]benzothiazine (4-EMPB) are synthetic compounds thought to have antineoplastic properties in PCa, which is achieved by promoting ferroptosis [ 151 ]. Qin et al synthesized isothiocyanate-modified AR antagonists, which showed synergistic activity when combined with buthionine sulfoximine to treat CRPC cells, and resulted in the downregulation of AR/AR-V7 and ferroptosis [ 152 ].…”
Section: Ferroptosis As a Promising Treatment In Pcamentioning
confidence: 99%